Inorganic phosphate, arsenate, and vanadate enhance exonuclease transcript cleavage by RNA polymerase by 2000-fold - Gottesman, Max E. (Proc Natl Acad Sci U S A, 2018)
Inorganic P(i) is involved in all major biochemical pathways. Here we describe a previously unreported activity of P(i). We show that P(i) and its structural mimics, vanadate and arsenate, enhance nascent transcript cleavage by RNA polymerase (RNAP). They engage an Mg(2+) ion in catalysis and activate an attacking water molecule. P(i), vanadate, and arsenate stimulate the intrinsic exonuclease activity of the enzyme nearly 2,000-fold at saturating concentrations of the reactant anions and Mg(2+). This enhancement is comparable to that of specialized transcript cleavage protein factors Gre and TFIIS (3,000- to 4,000-fold). Unlike these protein factors, P(i) and its analogs do not stimulate endonuclease transcript cleavage. Conversely, the protein factors only marginally enhance exonucleolytic cleavage. P(i) thus complements cellular protein factors in assisting hydrolytic RNA cleavage by extending the repertoire of RNAP transcript degradation modes.